1984
DOI: 10.1007/bf02396943
|View full text |Cite
|
Sign up to set email alerts
|

The effect of microcracking upon the Poisson's ratio for brittle materials

Abstract: Microcracking--elasticity theories typically relate a decrement in elastic moduli to the number density, N, and the mean microcrack radius (a). In this paper, four microcracking-modulus theories are rewritten in terms of the macroscopic, observable parameters of Young's modulus and Poisson's ratio, eliminating the specific dependence on the difficult to measure, microscopic quantities N and (a). The rewritten microcracking elasticity theories are then compared to elasticity data on a variety of m icrocracked, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…During the first cycle, we calculate a permanent decrease in vPvCWI0.25em from 1.84 to 1.34 (Figure ) due to thermal microcracking. We note that a vPvS0.25em ratio of less than 21.41 results in a negative Poisson's ratio and, although theoretically plausible (Case, ; Walsh, ), is rare among isotropic materials. Homand‐Etienne and Houpert () also found a negative Poisson's ratio for two thermally microcracked granites (Senones Granite and Remiremont Granite heated to 200–600°C); they suggested that residual stresses during cooling are the cause of this unexpected mechanical behavior.…”
Section: Discussionmentioning
confidence: 75%
“…During the first cycle, we calculate a permanent decrease in vPvCWI0.25em from 1.84 to 1.34 (Figure ) due to thermal microcracking. We note that a vPvS0.25em ratio of less than 21.41 results in a negative Poisson's ratio and, although theoretically plausible (Case, ; Walsh, ), is rare among isotropic materials. Homand‐Etienne and Houpert () also found a negative Poisson's ratio for two thermally microcracked granites (Senones Granite and Remiremont Granite heated to 200–600°C); they suggested that residual stresses during cooling are the cause of this unexpected mechanical behavior.…”
Section: Discussionmentioning
confidence: 75%
“…From these assumptions, E may be calculated from the measured V l as (2) where ρ is the mass density of the specimen and ν is Poisson's ratio. However, ν is also a function of microcracking, depending upon if the microcracks are open or have been compressed closed [26,27]. For open microcracks, the relative changes in E and ν were approximated for small changes by Walsh [26], with good agreement with experiments [27], as (3) where the subscript 0 denotes the initial (uncycled) value.…”
Section: Discussionmentioning
confidence: 76%
“…These discrepancies suggested the existence of internal strains inside the specimens. Further, the smaller elastic moduli of two-phase porcelains also suggested the existence of internal strains or cracks 14,15) . The degree of transparency of T-C porcelains decreased with an increase in cristobalite content.…”
Section: Discussionmentioning
confidence: 99%